Associations Between Clinical Evidence of Inflammation and Synovitis in Symptomatic Knee Osteoarthritis: A Cross-Sectional Substudy - Wallace, Gemma; Cro, Suzie; Dore, Caroline; King, Leonard; Kluzek, Stefan; Price, Andrew; Roemer, Frank; Guermazi, Ali; Keen, Richard; Arden, Nigel (Arthritis & Rheumatism-Arthritis Care & Research, 2017)
Painful knee osteoarthritis (KOA) has been associated with joint inflammation. There is, however, little literature correlating signs of localized inflammation with contrast-enhanced (CE) magnetic resonance imaging (MRI) of synovium. This study examined the relationship between clinical and functional markers of localized knee inflammation and CE MRI-based synovial scores.Patients with symptomatic KOA were enrolled into the randomized, double-blind, Vitamin D Evaluation in Osteoarthritis (VIDEO) trial. In this cross-sectional substudy, associations between validated MRI-based semiquantitative synovial scores of the knee and the following markers of inflammation were investigated: self-reported pain and stiffness, effusion, warmth, joint line tenderness, erythrocyte sedimentation rate, radiographic severity, and functional ability tests.A total of 107 patients satisfied the inclusion criteria of complete data and were included in the analysis. Significant associations were found between the number of regions affected by synovitis and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain, effusion, and joint line tenderness. Each additional region affected by synovitis was associated with an increase in WOMAC pain (1.82 [95% confidence interval (95% CI) 0.05, 3.58], P = 0.04), and the association with extent of medial synovitis was particularly strong (3.21 [95% CI 0.43, 5.99], P = 0.02). Extent of synovitis was positively associated with effusion (odds ratio 1.69 [95% CI 1.37, 2.08], P < 0.01) and negatively associated with joint line tenderness (relative risk 0.87 [95% CI 0.84, 0.90], P < 0.01).There is a strong positive association between synovitis and self-reported patient pain and clinically detectable effusion. Nonoperative treatments directed at management of inflammation and future trials targeting the synovial tissue for treating KOA should consider these 2 factors as potential inclusion criteria.
EVALuna2:14714